A review on application of waste cooking oil as rejuvenator in porous asphalt mixture - Wan Azahar, Wan Nur Aifa; Bujang, Mastura; Putra Jaya, Ramadhansyah; Hainin, Mohd Rosli; Ngadi, Norzita; Abdullah, Mohd Ezree; Mohamed, Abdullahi Ali (UTM Press, 2016)
Aging process of bitumen is one of the main obstacles, which limit the implementation of porous pavement. An aging process would cause a shorter service life of porous asphalt compared to the conventional hot mix asphalt mixture. The tendency rate of aging processes in porous asphalt is high due to the exposure of bitumen and aggregates binding in an open-graded structure that maximizes oxidation process to occur thus producing aged binder. In this respect to restore the original characteristics of pavement from aged bitumen, rejuvenation of bitumen binder offers an effective option. From the previous research, the performance of waste cooking oil (WCO) is investigated and indicated as one of rejuvenator agents for bitumen regeneration. Thus, this paper reviewed the novelty of the WCO, as an alternative natural rejuvenating agent for aged bitumen to a condition that resembles the original bitumen in the asphalt mixture.